Effect of Working Capital Turnover, Cash Turnover, Debt To Equity Ratio (DER) and Total Asset Turnover on Profitability - Anisa Vramita Gultom; Megaria Siringoringo; Geby Mutiara Hutagalung; Rahel Mey Lany Malau; Siti Aisyah Nasution; Anggono Anggono (Jurnal Ipteks Terapan, 2023)
Study This done For test Good in a manner simultaneous or partial . Effect of Working Capital Turnover, Cash Turnover, Debt to Equity Ratio, Total Asset Turnover Against Profitability (ROA) on banking sector companies listed on the Indonesia Stock Exchange on period 2019- 2021. Any data required official data from report finance originating year _ from IDX. Method in sampling using _ purposive sampling method. Tests used _ consists from test assumption classic that part That test normality , test multicollinearity , test autocorrelation , test heteroscedasticity , test multiple linear regression part That test coefficient determination (R2), test hypothesis in a manner partial ( T test ), test hypothesis in a manner simultaneously ( test F). The adjusted R Square value has influence of 12.5% against profitability (ROA) and the remaining 87.5% is influenced by other variables . Results from his research are : the working capital turnover variable has an effect negative on ROA, the Cash Turnover variable has an effect positive on ROA, the Debt To Equity variable has an effect No influential positive , variable Total Assets Turnover is not influential positive . WCT, CT, DER, TATO, effect in a manner simultaneous against ROA .